Effect of Aspect Ratio on the Evolution of Shear Bands in Zr61.7Al8Ni13Cu17Sn0.3 Bulk Metallic Glass. Issue 1 (January 2017) - Ma, Wenli; Xu, Yuanli; Shi, Bo; Li, Jiangong
Abstract : Zr61.7 Al8 Ni13 Cu17 Sn0.3 bulk metallic glass samples with different aspect ratios in the range of 0.25–2.25 were deformed by compression, and the effect of aspect ratio on the evolution of shear bands was investigated. It is found that for the deformed Zr61.7 Al8 Ni13 Cu17 Sn0.3 bulk metallic glass, the average shear band spacing decreases and the shear band density increases monotonically as the aspect ratio increases from 0.25 to 2.25. A minimal average shear band spacing of 0.478 µm is achieved for the sample with an aspect ratio of 2.25. In addition, the fractions of shear bands with spacings below 100 and 50 nm are about 12.84% and 6.76%, respectively, for the sample with an aspect ratio of 2.25. The reason for the formation of a higher density of shear bands can probably be attributed to the increase of the driving force for the sample with a larger aspect ratio.